Use of Various Ratios of Extruded Fullfat Soybean Meal and Dehulled Solvent Extracted Soybean Meal in Broiler Diets - Subuh, A.M.H.; Motl, M.A.; Fritts, C.A.; Waldroup, P.W. (International Journal of Poultry Science, 2001)
A study was conducted in which whole unextracted soybeans were processed by passing the beans through a roller mill and then extruding without steam. The processed beans were then included into nutritionally adequate broiler diets, replacing solvent extracted soybean meal in ratios of 0/100, 25/75, 50/50, and 0/100 % with dietary energy levels of 3200, 3300, and 3400 ME kcal/kg. This resulted in a 3 x 4 factorial arrangement of treatments. Each treatment was fed to six replicate pens of 60 male chicks of a commercial broiler strain from 1 to 42 days of age. The results of the study demonstrate that the inclusion of extruded fullfat soybean in a pelleted broiler diet supported chick performance equal or superior to that of dehulled solvent extracted soybean meal, and that extruded soybeans could partially or completely replace soybean meal without any adverse effects on body weight, feed conversion, mortality, dressing percentage, or abdominal fat content provided the diets are nutritionally balanced.